Transparency and participation in the global polity: lessons learned from food and water governance (Glocalism: Journal of Culture, Politics and Innovation, 2015)
Within the global polity several global regulatory regimes overlap and intersect without establishing one single and unitary legal order. Despite such fragmentation, each global regulatory regime constrains the behaviour of States and individuals through “induced compliance” and significantly impacts domestic regulation, influencing both the content and the way decisions are made. This also applies to the global regimes of food and water, where the interplay between different rules and actors (public/private, domestic/global) raises a number of questions on the complex relationship between the power makers that establish the rules and those who are affected by them. These regimes are particularly emblematic of the debate about the democratic quality of global polity. They also show the lack of balance among national governments, global institutions, and civil society organizations. As a matter of fact, at the global level, there is no directive representative democracy, but some forms of deliberative or procedural democracy, which emerge through the application of administrative procedures and formal guarantees in the decision-making processes. Among such tools, this article focuses on transparency and participation, which are two fundamental legal instruments featuring procedural legitimacy. The paper is divided in four sections. The last section contains three conclusive remarks: 1) an effective increment of transparency and participation in global decision-making would enhance pluralism, accountability and power-checking in the global polity; 2) even the increment of transparency and participation can present drawbacks, which need to be tackled and nullified by the application of specific procedural devices; 3) the main improvement would rely on procedural democracy as transparency and participation need to be combined with other administrative principles and guarantees, such as due process, duty to give reason, judicial review, and so on.
Keywords: transparency; participation; food; water; global governance